The use and subjective experience of sleep apps and their relationship with personality characteristics among young adults - Ståle Pallesen; Ståle Pallesen; Øystein Vedaa; Øystein Vedaa; Erlend Sunde; Erlend Sunde; Anette Harris; Siri Waage; Siri Waage; Ingvild West Saxvig; Jiewen Zhang; Bjørn Bjorvatn; et al. (Frontiers in Sleep)
IntroductionSleep app use has become widespread in recent years. Still, understanding of characteristics of users and the impact of sleep app usage remains limited.MethodsA sample of 940 young adults (18–30 years) living in the UK were recruited from Prolific (online research platform offering researchers access to survey panels) and invited to participate in a survey on the use and experience with sleep apps. Both sleep app users and non-users were invited. The survey included questions about demographics, morningness (Horne–Östberg Morningness–Eveningness Questionnaire-reduced scale), insomnia symptoms (Bergen Insomnia Scale), personality (HEXACO: Honesty-Humility, Emotionality, Extraversion, Agreeableness, Conscientiousness, and Openness to Experience), in addition to sleep app usage and how such use is experienced. A logistic regression analysis was conducted to identify characteristics of sleep app users. Factor analysis was used to elucidate dimensions of sleep app use experiences. Scores on the items making up each factor were then regressed on demographic variables, morningness, insomnia symptoms and personality.ResultsIn all, 36.8% of the participants reported using or having used sleep apps. Use was positively associated with age, insomnia symptoms, and conscientiousness. The factor analysis revealed three factors coined: trust/objectification (trust in sleep app results), negative (e.g., becoming stressed) and positive (e.g., prioritize sleep more) perceived effects. Trust/objectification was positively associated with age and agreeableness, and inversely related to high education and openness to experience. Insomnia symptoms and emotionality were associated with perceived negative effects. Morningness and male gender were associated with perceived positive effects whereas high education had an inverse relationship with perceived positive effects.DiscussionThe use of sleep apps was widespread. Different responses to sleep app usage were observed and linked to various individual variables. The findings suggest that perceived effects of sleep apps usage should be considered in light of individual differences. Research on sleep apps is still in its early stages, and several suggestions (recommendations) for future studies are outlined.